Comparative Proteomic Analysis of the Defense Response to Gibberella Stalk Rot in Maize and Reveals That ZmWRKY83 Is Involved in Plant Disease Resistance - Bai, Hua; Si, Helong; Zang, Jinping; Pang, Xi; Yu, Lu; Cao, Hongzhe; Xing, Jihong; Zhang, Kang; Dong, Jingao (Frontiers in Plant Science, 2021)
Fusarium graminearum is the causal agent of Gibberella stalk rot in maize stem, resulting maize lodging, yield, quality, and mechanical harvesting capacity. To date, little is known about the maize stem defense mechanism in response to invasion of F. graminearum. This study represents a global proteomic approach to document the infection by F. graminearum. A total of 1,894 differentially accumulated proteins (DEPs) were identified in maize stem with F. graminearum inoculation. Functional categorization analysis indicated that proteins involved in plant-pathogen interaction were inducible at early stages of infection. We also found that the expression of proteins involved in phenylpropanoid, flavonoid, and terpenoid biosynthesis were up-regulated in response to F. graminearum infection, which may reflect these secondary metabolism pathways were important in protection against the fungal attack in maize stem. In continuously up-regulated proteins after F. graminearum infection, we identified a WRKY transcription factor, ZmWRKY83, which could improve the resistance to plant pathogens. Together, our results show that the defense response of corn stalks against F. graminearum infection was multifaceted, involving the induction of proteins from various immune-related pathways, which had directive significance for molecular genetic breeding of maize disease-resistant varieties.